Pedagogical Preparation of Pre-service Primary School Teachers: The Challenges of the Professional Experience in Fiji - Victor Mafone Alasa; Fabiano Tikoinavuso; Taraivini Raramasi Raiula; Feroz Ali (Universitas Sultan Ageng Tirtayasa, 2021)
In many countries where funding for education has been directed at improving access, the redirection towards funding of quality education has been slow. In Fiji, studies have found that symptoms of the lack of funding for quality education include: large class sizes in urban areas; multi-grade classes in rural areas; low levels of qualifications in the teaching force; teachers’ general frustration with curriculum development; and the pressures of external examination systems as asystemmatic. In this context, the pressures on individual teachers are high, while support for them and for the schools they serve is low. An aspect that was discussed of the result of this ongoing pressure is the impact on pre-service teachers who become part of these school communities for their field experience (or practicum). This paper reports on the frustrations and disappointments expressed by one group of pre-service teachers as they reflect on their practicum experiences in schools in Fiji qualitative research design and data gathered were content analyzed. The findings shed light on the difficulties faced by all teachers in Fiji. Recommendations include not only supporting pre-service teachers during their practicum, but also supporting the teachers in the field whose responsibility for preparing the new generation of teachers is sometimes taken for granted.